Optimalisasi Komersial Usaha Batik Al-Barokah Melalui Digital Marketing Dalam Menjaga Competitive Advantage - Shalehoddin, Shalehoddin; Yakin, Ainol; Devita, Putri (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
In the rapidly evolving era of digitalization in 2024, the batik business Al-Barokah has successfully increased its revenue through innovative digital marketing strategies. Through qualitative research with a case study approach, the use of social media platforms such as Facebook, Instagram, and WhatsApp has proven effective in disseminating information, creating positive perceptions, and expanding the market reach for batik products. Despite facing intense competition, Al-Barokah batik continues to innovate with unique product quality, utilizing website design features and visual videos to promote its products. With the right digital marketing approach, Al-Barokah has significantly increased its revenue in 2024, emphasizing the strategic role of digital marketing in enhancing competitiveness and sustainability in the current digital era.